Friends, lovers, and the big terrible thing a memoir - Perry, Matthew 1969-2023; Kudrow, Lisa (Waterville, ME Thorndike Press, a part of Gale, a Cengage Company, 2022)
Perry takes readers behind the scenes of the sitcom Friends-- and into his struggles with addiction. Vividly detailing his lifelong battle with alcoholism and drugs, he examines what fueled it despite seemingly having it all: the desire for recognition that drove him, the void inside him that could not be filled, and the peace he's found in sobriety. -- adapted from back cover
Foreword / by Lisa Kudrow -- Prologue -- The view -- Interlude : New York -- Another generation shot to hell -- Interlude : Matman -- Baggage -- Interlude : Dead -- Like I've been there before -- Interlude : Zoom -- No fourth wall -- Interlude : Holes -- Bruce Willis -- Interlude : All heaven breaking loose -- The benefit of Friends -- Interlude : Pockets -- Odyssey -- Interlude : Trauma camp -- Three's not company, three ruins everything -- Interlude : Violence in Hollywood -- The big terrible thing -- Interlude : The smoking section -- Batman.
"Thorndike Press large print basic."
112751
Keywords: Perry, Matthew, -- 1969-2023.; Friends (Television program); Actors -- United States -- Biography; Addicts -- United States -- Biography; Substance abuse -- United States; United States; Large type books; autobiographies (literary works); Large print books; Biographies